Carbon-based magnetic composite material, and preparation method and application of columnar structure microwave absorber
Through the mixing of carbon-based magnetic composite materials with spherical carbonyl iron powder and graphite, combined with columnar structure and 3D printing technology, the problem of complex preparation of existing microwave absorbing materials and incompatible frequency bands is solved, and low-cost and high-performance broadband microwaves are achieved Absorption, suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411461280.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-07
Smart Images

Figure CN119275596A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electromagnetic microwave absorption, and more specifically, relates to a carbon-based magnetic composite material, a columnar structure microwave absorber, and a preparation method and application thereof. Background Art
[0002] In the information age, the popularity of a large number of electronic communication devices has led to the emergence of electromagnetic radiation in the living environment that cannot be ignored. These electromagnetic radiations will affect human health to a certain extent and interfere with the normal operation of precision electronic instruments and equipment. In addition, in the military field, the advancement of radar detection technology has also put forward higher requirements for military stealth technology. The stealth and protection of military equipment urgently need higher-performance electromagnetic wave absorption layers. Therefore, whether in the civilian or military fields, low-cost, high-performance microwave absorbers are urgently needed to achieve the needs of stealth and protection.
[0003] In order to ensure strong absorption of electromagnetic waves, existing high-performance microwave absorbing materials often combine different loss mechanisms of multiple materials for electromagnetic waves, and the preparation process is relatively complicated, which cannot meet the requirements of low cost and large-scale production, greatly limiting the practical application of microwave absorbers. In addition, a single microwave absorbing material cannot achieve broadband microwave absorption while having strong microwave absorption performance. Its absorption band range cannot cover 5-15 GHz or even X-band (8-12 GHz). This problem of incompatibility between absorption intensity and absorption bandwidth puts forward higher requirements for the preparation and design of microwave absorbers. Summary of the invention
[0004] The purpose of the present invention is to make up for the shortcomings of existing microwave absorbers and propose a low-cost broadband absorption columnar microwave absorber. The columnar microwave absorber has broadband absorption performance while maintaining low-cost preparation, and can guarantee -10dB microwave absorption performance in 5-18GHz, while the average absorption rate in the X-band (8-12GHz) can reach -20dB.
[0005] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0006] A method for preparing a carbon-based magnetic composite material comprises the following steps: fully carbonizing the pretreated biomass material in a protective gas atmosphere at a temperature of 600 to 800°C, cooling it, and then mixing and grinding it evenly with spherical carbonyl iron powder and graphite in a certain proportion to obtain the desired carbon-based magnetic composite material.
[0007] Preferably, the biomass material is selected from purchased almond husks or reeds; and the pretreatment includes crushing and washing.
[0008] Preferably, the spherical carbonyl iron powder is selected from commercial spherical carbonyl iron in the market, the main chemical components of which are Fe, C, and O, the real part of the dielectric constant of which is between 22 and 25, and the real part of the magnetic permeability of which is between 2.5 and 3.1.
[0009] Preferably, the graphite is 750-850 mesh graphite powder purchased from the market.
[0010] Preferably, the carbonization time is 2 to 3 hours.
[0011] Preferably, the grinding time is 0.5 to 1 h.
[0012] Preferably, the biomass carbon material accounts for 10% to 30% of the total composite material, the spherical carbonyl iron accounts for 50% to 80% of the total composite material, and the graphite accounts for 0% to 20% of the total composite material.
[0013] The present invention also provides a columnar structure microwave absorber, which is a double-layer columnar structure of a unit periodic array and is distributed on a metal plate in an N*N periodic array, where N is a positive integer.
[0014] The columnar structure microwave absorber comprises a shell, a lossy material layer and a metal plate layer.
[0015] The shell wraps a lossy material layer, and the lossy material layer is located on the metal plate layer.
[0016] The lossy material layer is made of the carbon-based magnetic composite material and paraffin or epoxy resin.
[0017] The carbon-based magnetic composite material accounts for 50% to 90% of the weight of the lossy material layer.
[0018] The material layer is a square column structure placed on a bottom square flat plate.
[0019] The bottom flat plate structure of the material layer has a side length a and a thickness h1, and the upper square column structure has a side length b and a thickness h2. The a is 8-12 mm, the b is 2.6-3 mm, the h1 is 0.1-1 mm, and the h2 is 4-6 mm. All the above dimensions do not include the shell thickness t, but only the dimensions of the lossy material layer itself. These parameters of the lossy material layer have a greater impact on the absorbing performance, and too large or too small will affect the absorbing performance. Preferably, the thickness of the shell is t, and t is 0.3-1 mm; the thickness d of the bottom metal plate is 0.2-1 mm. The purpose of the shell is to provide shape support. If the thickness is too thin, it is easy to break. If it is too thick, it will easily increase the printing preparation time and the quality of the finished product. Therefore, it is necessary to select a suitable shell thickness; the role of the metal plate at the bottom of the columnar structure microwave absorber is to reflect electromagnetic waves. No matter how thick it is, it can be completely reflected. Considering that light absorbers have a wider range of applications, the thickness is selected as thin as possible.
[0020] The shell is a commonly used 3D printing material.
[0021] The commonly used 3D printing materials include polylactic acid plastic, ABS plastic and polycarbonate plastic.
[0022] The bottom metal plate layer includes a copper plate, an iron plate and an aluminum plate.
[0023] The thickness of the bottom metal plate is 0.2-1 mm.
[0024] The shell is printed by a fused deposition modeling 3D printer.
[0025] The 3D printing conditions are: printing temperature of 150-250° C., printing accuracy of 0.05-0.25 mm, minimum layer thickness of the nozzle of 0.02-0.08 mm, printing speed of 1-8 mm / s, and filling rate of 100%.
[0026] The method for preparing the unit structure of the columnar structure microwave absorber comprises the following steps: preparing a carbon-based magnetic composite material according to the above method, uniformly dispersing the obtained carbon-based magnetic composite material in molten paraffin or epoxy resin to obtain a loss material, injecting the obtained loss material into a shell, and cooling and molding at room temperature to obtain the result.
[0027] In addition, the present invention also provides the application of the carbon-based magnetic composite material or the columnar structure microwave absorber in the field of electromagnetic wave absorption. The present invention has the following beneficial effects:
[0028] The carbon-based magnetic composite material of the present invention is made by mixing and grinding waste biomass materials after carbonization treatment with commercially available spherical carbonyl iron powder, and the preparation method is simple; the composite material has the advantages of low cost and excellent microwave absorption performance; and the preparation scheme of the composite material is simple, and no additional polluting waste is generated. The composite material is applied to the preparation of a columnar microwave absorber, and its microwave absorption performance is greatly improved, while the weight of the microwave absorber is reduced, and the surface density of the columnar microwave absorber is effectively reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 These are SEM images of the carbon-based magnetic composite samples prepared in Examples 1 and 2.
[0030] Figure 2 The complex dielectric constant and complex magnetic permeability of the carbon-based magnetic composite material prepared in Examples 1 and 2.
[0031] Figure 3 The reflection loss is calculated from the electromagnetic parameters of the carbon-based magnetic composite materials prepared in Examples 1 and 2.
[0032] Figure 4 This is a structural diagram of the columnar structure microwave absorber made in Examples 1 and 2.
[0033] Figure 5 This is a physical picture of the columnar structure microwave absorber made in Examples 1 and 2.
[0034] Figure 6 This is a reflection loss diagram of the columnar structure microwave absorber made in Examples 1 and 2 tested in a microwave darkroom. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0036] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0037] Example 1 A microwave absorber made of a carbon-based magnetic composite material
[0038] 1. Experimental methods
[0039] The raw material is almond shell, which is crushed and ultrasonically cleaned three times with deionized water, and then placed in an oven to dry at 40°C for 24 hours. It is calcined in a tubular furnace at 800°C for 2 hours under a flowing nitrogen atmosphere, with a heating rate of 10°C / min. After cooling to room temperature, it is mixed and ground evenly with spherical carbonyl iron powder in a ratio of 3:7 to obtain a carbon-based magnetic composite material.
[0040] Then, the 3D printer was set to a printing temperature of 210°C, a printing accuracy of 0.01mm, a minimum layer thickness of 0.05mm, a printing speed of 6mm / s, and a filling rate of 100%. The shell was printed by a fused deposition modeling 3D printer, and then the carbon-based magnetic composite material obtained above was evenly dispersed in the molten paraffin to obtain a loss material. The magnetic biomass carbon-based composite material accounted for 80% of the total weight of the loss material. The loss material was then injected into the 3D printed model shell and cooled at room temperature to obtain the shell. The shell of the columnar structure microwave absorber is as follows: Figure 4 As shown, its dimensions are: a = 10mm, b = 5.6mm, h1 = 0.7mm, h2 = 4.8mm. The thickness of the outer shell t is 0.5mm, the thickness of the bottom metal plate is 0.2mm, the middle loss layer material is the carbon-based magnetic composite material produced above, and the total height of the loss material layer is 5.5mm. The actual picture of the columnar structure microwave absorber is as follows Figure 5 As shown in a.
[0041] 2. Experimental results
[0042] Scanning electron microscopy (SEM) was used to study the surface morphology and microstructure of the carbon-based magnetic composites after pyrolysis. Figure 1 As shown in a, it can be seen that the biochar presents a hierarchical porous structure, and the spherical carbonyl iron powder is evenly dispersed in the pore structure of the biochar. This porous structure and the distribution of spherical carbonyl iron are conducive to the scattering and reflection of electromagnetic waves. The electrical loss of the carbon material and the magnetic loss of the carbonyl iron are conducive to the loss of the energy of the electromagnetic wave.
[0043] The sample of carbon-based magnetic composite material mixed with paraffin was then pressed into a coaxial sample ring through a mold, and the complex dielectric constant and complex magnetic permeability of the material were measured using a vector network analyzer, and the reflection loss value of the material at different thicknesses was calculated based on the transmission line theory. Figure 2 As shown in a, the reflection loss is Figure 3 As shown in a. Figure 2 The complex magnetic permeability curve in a confirms that the composite material has magnetic properties. Figure 3 The absorption loss graph confirms that the maximum reflection loss of the carbon-based magnetic composite material obtained in Example 1 is -38dB at 3mm, the maximum absorption peak is at 3.12GHz, and the absorption bandwidth is 1.92GHz. The maximum absorption bandwidth is 4.32GHz, and the thickness is 1.4mm. As the thickness increases, its absorption peak gradually moves from high frequency to low frequency.
[0044] The reflection loss RL of the columnar structure microwave absorber was measured by the free space far-field reflectivity test method in a microwave darkroom. The results are as follows: Figure 6As shown. The columnar structure microwave absorber achieves ultra-wideband effective absorption of up to 90% in the 3.4-18 GHz band, and the absorption bandwidth is 14.6 GHz. In addition, the columnar structure microwave absorber in Example 1 can achieve 96% electromagnetic wave absorption in the X-band, and its average absorption rate can reach 99%. The unique graded porous structure of the loss material helps to improve the impedance matching performance, increase the electromagnetic loss, and allow electromagnetic waves with a wider frequency to enter the absorber, further improving the microwave absorption performance. Ultra-wideband absorption is closely related to the periodic structure, which produces multiple resonances as well as edge diffraction and scattering effects.
[0045] Example 2 A columnar structure microwave absorber made of a carbon-based magnetic composite material
[0046] 1. Experimental methods
[0047] Reeds were used as the raw material, which was crushed and ultrasonically cleaned three times with deionized water, and then dried in an oven at 40°C for 24 hours. The raw material was calcined in a tubular furnace at 800°C for 2 hours under a flowing nitrogen atmosphere at a heating rate of 10°C / min. After cooling to room temperature, the raw material was mixed and ground with spherical carbonyl iron powder and graphite in a ratio of 1:8:1 to obtain a carbon-based magnetic composite material.
[0048] Then, the 3D printer was set to a printing temperature of 210°C, a printing accuracy of 0.01mm, a minimum layer thickness of 0.05mm, a printing speed of 6mm / s, and a filling rate of 100%. The shell was printed by a fused deposition modeling 3D printer, and then the carbon-based magnetic composite material obtained above was evenly dispersed in the molten paraffin to obtain a loss material. The magnetic biomass carbon-based composite material accounted for 80% of the total weight of the loss material. The loss material was then injected into the 3D printed model shell and cooled at room temperature to obtain the shell. The shell of the columnar structure microwave absorber is as follows: Figure 4 As shown, its dimensions are: a = 8mm, b = 4.8mm, h1 = 0.2mm, h2 = 4.4mm. The thickness of the outer shell t is 0.5mm, the thickness of the bottom metal plate is 0.2mm, the middle loss layer material is the carbon-based magnetic composite material produced above, and the total height of the loss material layer is 4.6mm. The actual picture of the columnar structure microwave absorber is as follows Figure 5 As shown in b.
[0049] 2. Experimental results
[0050] Scanning electron microscopy (SEM) was used to study the surface morphology and microstructure of the carbon-based magnetic composites after pyrolysis. Figure 1 As shown in b, it can be seen that the graphite is in a flake structure, and the carbonyl iron powder is in the form of small spheres mixed with flake graphite and dispersed on the surface of the reed biochar, among which there are a few smaller reed biochar fragments. Figure 1The composite material in Example 2 mainly dissipates the energy of electromagnetic waves through the electrical loss properties of reed biochar and graphite and the magnetic loss properties of carbonyl iron.
[0051] The sample of carbon-based magnetic composite material mixed with paraffin was then pressed into a coaxial sample ring through a mold, and the complex dielectric constant and complex magnetic permeability of the material were measured using a vector network analyzer, and the reflection loss value of the material at different thicknesses was calculated based on the transmission line theory. The complex dielectric constant and complex magnetic permeability curves of the composite material are shown in Figure 2. Figure 2 As shown in b, the absorption loss diagram of the composite material is as follows Figure 3 b. The complex magnetic permeability curve also confirms that the carbon-based magnetic composite material obtained in Example 2 has magnetism, and the real part of the dielectric constant is slightly higher than that in Example 1. In addition, the carbon-based magnetic composite material obtained in Example 2 has a maximum reflection loss of -53.1dB at 4.2mm, a maximum absorption peak at 2.16GHz, and an absorption bandwidth of 0.88GHz. Its maximum absorption bandwidth is 3.68GHz, and the thickness is 1.6mm at this time. As the thickness increases, its absorption peak gradually moves from high frequency to low frequency.
[0052] The reflection loss RL of the columnar structure microwave absorber was measured by the free space far-field reflectivity test method in a microwave darkroom. The results are as follows: Figure 6 As shown. The columnar structure microwave absorber achieves broadband effective absorption of up to 90% in the 5.01-18 GHz band, and the absorption bandwidth is 12.99 GHz. In addition, the columnar structure microwave absorber of Example 2 can achieve 96% electromagnetic wave absorption in the X-band, and its average absorption rate can reach 99% in the 5-15 GHz band. Its absorption mechanism is similar to that of Example 1.
Claims
1. A method for preparing a carbon-based magnetic composite material, characterized in that: The following steps are involved: The pretreated biomass material is fully carbonized in a protective gas atmosphere at a temperature of 600-800° C., cooled, and mixed and ground evenly with spherical carbonyl iron powder and graphite in a certain proportion to obtain the desired carbon-based magnetic composite material.
2. The preparation method according to claim 1, characterized in that: The biomass material is selected from any one of almond husks, reed stalks, corn cobs, and walnut shells; and the pretreatment includes washing, cutting or crushing.
3. The preparation method according to claim 1, characterized in that: The spherical carbonyl iron powder and graphite are both commercial products available in the market; the main chemical components of the carbonyl iron powder are Fe, C, and O, the real part of its dielectric constant is between 22 and 25, and the real part of its magnetic permeability is between 2.5 and 3.1; the graphite is 750-850 mesh graphite powder.
4. The preparation method according to claim 1, characterized in that: In the mixed grinding ratio, the proportion of biochar is 10% to 30%, the proportion of spherical carbonyl iron is 50% to 80%, and the proportion of graphite is 0% to 20%.
5. The carbon-based magnetic composite material prepared by the preparation method according to any one of claims 1 to 4.
6. A columnar microwave absorber, characterized in that: The invention is a double-layer columnar structure periodic array distributed in N×N in a two-dimensional plane, wherein N is a positive integer; the unit structure comprises an outer shell, a lossy material layer and a metal plate layer; the outer shell wraps the lossy material layer, and the lossy material layer is located on the metal plate layer; the unit structure is a double-layer columnar structure, wherein the bottom layer is a thin square flat plate and the upper layer is a square column structure; the lossy material layer is made of the carbon-based magnetic composite material described in claim 5 and paraffin or epoxy resin.
7. The columnar structure microwave absorber according to claim 6, characterized in that: The lossy material layer is a double-layer columnar structure composed of a square column structure placed on a thinner square flat plate; wherein the bottom flat plate structure has a side length a and a thickness h1, and the upper square column structure has a side length b and a thickness h2; a is 8 to 12 mm, b is 2.6 to 3 mm, h1 is 0.1 to 1 mm, and h2 is 4 to 6 mm.
8. The columnar structure microwave absorber according to claim 6, characterized in that: The thickness of the shell is t, and t is 0.3-1 mm; The thickness d of the bottom metal plate is 0.2-1 mm.
9. The columnar structure microwave absorber according to claim 6, characterized in that: The mass proportion of the carbon-based magnetic composite material in the lossy material layer is 50% to 90%.
10. Use of the carbon-based magnetic composite material according to claim 5 or the columnar structure microwave absorber according to any one of claims 6 to 9 in the field of electromagnetic wave absorption.
Citation Information
Patent Citations
Wave-absorbing material based on grapheme and preparation method thereof
CN105647468A
Magnetic biomass carbon-based composite material, metamaterial microwave absorber and preparation method and application of magnetic biomass carbon-based composite material and metamaterial microwave absorber
CN116435081A
Microwave absorbing material as well as preparation method and application thereof
CN118183866A